A tributação seletiva no IPI e no ICMS: indeterminação e controle do conceito de essencialidade - Farias, Luiz Roberto Barros (2017)
The present dissertation intends to present proposals to control the indeterminacy of the legal concept of essentiality, a criterion used in the selective taxation of the IPI and ICMS, which prescribes that essential goods must suffer lower taxation than luxury ones. The work consists of four chapters, besides the introduction and conclusion. In the first one, we made na overview of the treatment of selective taxation conducted by Brazilian doctrine, drawing its correlation with the principle of equality, principle of ability to pay and extrafiscal function of taxes, as well as analyzing the similarities and differences of the selectivity in the IPI and ICMS. Secondly, we study the concept of essentiality with support in the theory of indeterminate legal concepts, highlighting the problems of interpretation and discretion, and how this theory can contribute to the graduation of the essentiality of taxable goods, in a constitutionally way. In the third chapter, we present some possible solutions to reduce the high level of indeterminacy of the essentiality concept, based on the instruments and mechanisms provided in the Constitutional Tax System, such as complementary tax law, ordinary law, decree, Federal Senate resolutions and public participation. Finally, the last chapter examines the judicial review of the concept of essentiality, with the critical analysis of selected cases.